Akuntabilitas Publik dalam Tata Kelola Madani Street Food Sebagai Ruang Ekonomi dan Ruang Publik Perkotaan - Khairunsyah Purba; Meylan Anjely; Nurmaini Dalimunthe (Policy, Law and Political Research Center, 2026)
This study examines public accountability in the management of urban street food with a case study of Madani Street Food in Pekanbaru City. This research is motivated by the lack of information transparency, the absence of a public clarification mechanism, and the absence of evaluation and corrective actions. This study uses a qualitative approach with data collection through in-depth interviews with selected key informants, including street food vendors and Koperasi Primkopkar 0301 Pekanbaru. Data analysis consists of data reduction, data presentation, and conclusion drawing using Mark Bovens’ public accountability theoretical framework, which emphasizes four dimensions: informing, justification, questioning, and consequences. The results show that public accountability in the management of Madani Street Food is still weak and has not been systematically institutionalized. Information regarding management mechanisms and financial arrangements is not clearly conveyed to vendors, decision-making is not accompanied by adequate explanations, space for public clarification is very limited, and there is no evaluation and sanction mechanism. These conditions indicate that accountability practices remain administrative rather than substantive. Strengthening public accountability mechanisms is important to improve governance performance and realize fair, transparent, and sustainable urban street food management.